Aspekty řízení lidských zdrojů v organizacích: studie vztahů mezi manažery a zaměstnanci prostřednictvím teorie LMX - Pronina, Elizaveta (Vysoké učení technické v Brně. Fakulta podnikatelská, 2024)
Bakalářská práce se zaměřuje na zkoumání vztahů mezi manažerem a podřízeným. V teoretické části jsou definovány literární rešerše a klíčové pojmy. V analytické části je prostřednictvím dotazníkového šetření a metody LMX zjišťován a hodnocen současný stav ve vybraném podniku. Na základě analýzy získaných informací jsou v poslední části práce prezentovány návrhy a doporučení na zlepšení této problematiky.

The bachelor thesis focuses on the examination of the relationship between manager and subordinate. The theoretical part defines the literature search and key concepts. In the analytical part, the current state of affairs in the selected company is identified and evaluated through a questionnaire survey and the LMX method. Based on the analysis of the obtained information, suggestions and recommendations for improvement are presented in the last part of the thesis.
Aspects of human resource management in organizations: a study of manager-employee relations through LMX theory
Keywords: manažer; LMX; podřízený; vztahy na pracovišti; fluktuace zaměstnanců; komunikace; manager; LMX; subordinate; workplace relations; employee turnover; communication